Basins of attraction for chimera states - Erik A Martens; Mark J Panaggio; Daniel M Abrams (New Journal of Physics, 2016)
Chimera states—curious symmetry-broken states in systems of identical coupled oscillators—typically occur only for certain initial conditions. Here we analyze their basins of attraction in a simple system comprised of two populations. Using perturbative analysis and numerical simulation we evaluate asymptotic states and associated destination maps, and demonstrate that basins form a complex twisting structure in phase space. Understanding the basins’ precise nature may help in the development of control methods to switch between chimera patterns, with possible technological and neural system applications.